Biobased flame retardants from tartaric acid and derivatives. (November 2018) - Howell, Bob A.; Sun, Wenxiao
Abstract: Biobased flame retardants represent attractive alternatives to traditional organohalogen compounds which are persistent in the environment, tend to bioaccumulate and may pose risks to human health. Tartaric acid is generated annually in great abundance as a by-product of wine making. It is nontoxic and widely used as a food ingredient. It is tetrafunctional which provides broad opportunity for conversion to a wide spectrum of useful materials. It has been used as a base for the generation of a variety of new compounds that display good flame retardancy in DGEBA (diglycidyl ether of bis -phenol A) epoxy. These range from simple phosphinate and phosphonate esters to oligomeric materials containing bromine, in both saturated and unsaturated units, or bromine and phosphorus.